Analisis Kebutuhan LKPD Berbasis Model Problem Based Learning Pada Pembelajaran Matematika SMP - Nilza Humaira Salsabila; Sripatmi Sripatmi; Ratna Yulis Tyaningsih; Dwi Novitasari; Tabita Wahyu Triutami (EVOLUSI: JOURNAL OF MATHEMATICS AND SCIENCES, 2023)
The purpose of this research is to describe the results of the analysis of the needs of junior high school mathematics teachers towards the development of problem-based learning worksheet learning media to improve the numeracy skills. This research is part of development research which consists of 3 phases based on Plomp namely, Preliminary Research phase, Development phase, and Assessment phase. This research is in the Preliminary Research phase to analyze the needs of product or media development. The product developed in this study is a worksheet learning media based on the Problem Based Learning model. The subjects in this study were 18 junior high school math teachers, consisting of 10 males and 8 females. The data collection technique used in this study is a non-test technique using a research instrument in the form of a questionnaire. The questionnaire compiled is related to the needs of junior high school mathematics teachers for the development of problem-based learning worksheets. The results of the study show that the mathematics teacher agrees that Problem-Based Learning-based LKDP learning media needs to be developed to assist in improving students' numeracy skills.